Strasse in Neapel. - Bibliographisches Institut (Hildburghausen) (Hildburghausen : Bibliographisches Institut in Hildburghausen, 1800)
Prikaza ulice s tržnicom.
Dolje sredina ispod prikaza otisnuto: STRAASE in NEAPEL // Bibliograph. Institut in Hildburghausen.
Izvornik digitaliziran
Keywords: Napulj; Nadorezi